Force and motion - Fable Multimedia ([Northern Ireland, UK] : Fable Multimedia, 2000)
The CD-ROM has 11 interactive teaching tools that combine simulation , game - like graphics to bring topics such as terminal relocity and motion - time graphs to life
Windows system requirement : Pentium 75 Mhz processor ; 16 MB RAM ; Windows 95/98/NT/2000 ; 5 MB free hard disc space ; 256 - color or higher graphics card 16 bit ; 14' SVGA monitor
Macintosh system requirement : Power Macintosh Processor or better ; OS System 7 or higher ; 16 MB RAM ; 5 MB free hard disc space ; 14' 256 - color monitor ; CD-ROM drive
Keywords: Mathematical physics -- Graphic methods; Graphic methods; Motion; Force and energy; Speed -- Study and teaching